Relationship Between Fish Oil Use and Incidence of Primary Liver Cancer: Findings From a Population-Based Prospective Cohort Study - Jiang, Wei; Li, Fu-Rong; Yang, Huan-Huan; Chen, Guo-Chong; Hua, Yong-Fei (Frontiers in Nutrition, 2021)
Background: N-3 long-chain polyunsaturated fatty acids prevented nonalcoholic steatohepatitis and hepatocellular carcinoma (HCC) in studies of mouse models. We examined prospective relationships between fish oil use and risk of primary liver cancer and the major histological subtypes including HCC and intrahepatic cholangiocarcinoma (ICC). Methods: We included 434,584 middle-aged and older men and women who were free of cancer at recruitment of the UK Biobank (2006-2010). Information on fish oil use and other dietary habits was collected via questionnaires. Cox proportional hazards models were used to compute hazard ratio and 95% CI of liver cancer associated with fish oil use, with adjustment for socio-demographic, lifestyle, dietary, and other clinical risk factors. Results: At baseline, 31.4% of participants reported regular use of fish oil supplements. During a median 7.8 years of follow-up, 262 incident liver cancer cases were identified, among which 127 were HCC and 110 were ICC cases. As compared with nonusers, fish oil users had significantly 44% (95% CI: 25%-59%) lower risk of total liver cancer, and 52% (95% CI: 24%-70%) and 40% (95% CI: 7%-61%) lower risk of HCC and ICC, respectively. Higher intake of oily fish also was associated with lower risk of HCC (≥2 vs. <1 serving/week: hazard ratio = 0.46; 95% CI: 0.23-0.96; P-trend = 0.027) but not ICC (P-trend = 0.96). Conclusion: Habitual use of fish oil supplements was associated lower risk of primary liver cancer regardless of cancer histological subtypes, potentially supporting a beneficial role of dietary n-3 long-chain polyunsaturated fatty acids in liver cancer prevention.